hMSC exosomes as a novel treatment for female sensitive skin: An in vivo study - Ye, Congxiu; Zhang, Yunqing; Su, Zhen; Wu, Shuxia; Li, Yuxia; Yi, Jinling; Lai, Wei; Chen, Jian; Zheng, Yue (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Recent studies have reported that the incidence of sensitive skin is increasing. Skin sensitivity and skin barrier functions were related to many skin diseases including atopic dermatitis, psoriasis, rosacea, and so on. Mesenchymal stem cell (MSC)-derived exosomes (hMSC) might be considered as a new effective therapeutic scheme. Aims: This study aims to investigate the safety and efficacy of hMSC exosomes as a novel topical treatment for sensitive skin. Patients/Methods: Exosomes were extracted from Primary hMSC via ultracentrifugation method. The morphology of hMSC exosomes was studied via transmission electron microscope. Expression of exosome specific surface marker was detected via Western blot. 22 subjects (female, aged 18-55) diagnosed with sensitive skin were enrolled. Follow-up was conducted before, 7-day, 14-day, and 28-day after hMSC exosomes use. Transepidermal water loss (TEWL), surface hydration, sebum secretion, and L*a*b* value were simultaneously tested at the same time point in an environment‐controlled room. Results: Under transmission electron microscopy, the extracted hMSC exosomes were circular or elliptical with intact membrane structure, and their diameters ranged mainly from 40 to 80 nm. Western blot showed that the expression of markers CD63, CD9, and Tsg101 was positive. Brownian motion based nanoparticle trajectory analysis (NTA) showed that the main peak of particle size distribution occurred around 96 nm, the average particle size was 122 nm, and the main peak accounted for 96.7%. All this conformed to the biological characteristics of exosomes standardized by the International Society for Extracellular Vesicles. In the clinical trial, scores of objective symptoms including roughness, scales, erythema, and subjective symptoms including tension, burning, or itching, were improved after 7-, 14-, and 28- day using hMSC-exosomes. TEWL, hydration, sebum, Ph, and L* a* values were tended to healthy skin indexes. Conclusions: The hMSC-exosomes, with the advantages of biocompatibility and biodegradability, could improve clinical symptoms and eruptions in sensitive skin patients, and might be as an MSC cell-free novel therapy in sensitive skin-related disease treatment.